Xiong Shili's Treatise on Reality and Function - Makeham, John (Oxford Chinese Thought Series, 2023)
Xiong Shili (1885-1968) is widely recognized as a founding figure of the modern New Confucian school of philosophy and seen by many as one of the most important and creative Chinese philosophers of the twentieth century. Treatise on Reality and Function (Ti yong lun) is the mature expression of Xiong's signature metaphysical doctrine and sets out his developed account of his Confucian philosophy of mind and nature. This annotated translation by John Makeham presents the full text in English for the first time, along with the original foreword attributed to Han Yuankai, and Xiong's original preface.